Alberto Flores Galindo: marco sociopolítico, fronteras teóricas y proyecto político - Ruíz Zevallos, Augusto (2011)
This article aims to lead to a deeper understanding of the political project of Alberto Flores Galindo by examining his intellectual work as an historian. It will begin from an internal perspective by looking at the dynamics involved in the incorporation of theoretical and methodological approaches in which Marxist concepts predominate but then which begin to assimilate non-Marxist concepts and currents. At the same time emphasis on structures gives way to emphasis on subjective interpretations. This dynamics of incorporation came to be the theoretical operating mode which he used as an historian and political intellectual which from 1980 on he began to develop as an intellectual construct for the Peruvian left. In order to understand this development we also need to look at the external context, that is, the social, political, and ideological background which allowed him to go beyond his theoretical frontier and fix new limits. In other words, the changing political ambience in Peru influenced the changes in his political and historical thought.